Human resource management practices and firm outcomes: evidence from Vietnam - Dang, Thang (University of Economics Ho Chi Minh City, 2023)
Purpose The purpose of this paper is to estimate the effects of human resource management (HRM) practices on firm outcomes at the firm level in Vietnam. Design/methodology/approach The paper employs a fixed-effects framework for the estimation using a panel sample of manufacturing firms from small- and medium-sized enterprise surveys between 2009 and 2013. Findings The paper finds that, on average, a firm that provides the training for new workers gains roughly 13.7, 10 and 14.9 percent higher in output value per worker, value added per worker and gross profit per worker, respectively, than the counterpart. Moreover, an additional ten-day training duration for new employees on average leads to a 4.1 percent increase in output value per worker, a 3.0 percent rise in value added per worker and a 3.0 percent growth in gross profit per worker. The paper also uncovers that a marginal 10 percent of HRM spending results in about 2 and 1.6 percent rises in output value per worker and value added per worker, respectively. Originality/value Using the case of Vietnam, this paper shows the important roles of HRM practices in explaining firm outcomes.